Composição química e bioacessibilidade de minerais em melado de cana e farinhas de frutas - Galvão, Fernanda (2021)
Besides being sources of nutrients, foods can also be important allies in preventing diseases and maintaining quality of life. Thereby, a constant increase in the consumption of natural, minimally processed and/or functional foods has been observed. This makes it important to assess the composition and nutritional value of these products. Thus, this study aimed to evaluate the chemical and elemental composition and bioaccessibility of minerals in cane syrups and fruit flours, in addition to the contribution of these products to the recommended daily intake of minerals. The optimization and validation of fast and efficient methods for the determination of chromium and reducing capacity in cane syrup were also carried out. For chromium determination by GF AAS, a slurry sampling method was used, with the simple dissolution of the sample in ultrapure water. Method validation was carried out by evaluating parameters such as linearity, detection and quantification limits, precision and accuracy. The analytical curve was prepared by external standardization and low values of detection and quantification limits were found (7.2 and 22.0 ng g-1, respectively). The repeatability and intermediate precision estimates demonstrated that the method presents an adequate precision (RSD < 20%). The accuracy assessed by the recovery rates (102-113%) and the comparison with the reference method (t = 0.61; p = 0.562) was also adequate. For the determination of reducing capacity in cane syrup, a simplex centroid mixture design was applied to optimize the composition of the extracting solvent and a Box-Behnken design was used to optimize the conditions of sample weight, extraction time and HCl concentration. The optimal conditions established by the experimental designs were: 6.0 ml of solvent (1.6 ml of 90% ethanol + 4.4 ml of water) without addition of HCl, 0.1 g of sample and 10 minutes of extraction. The method validation showed the possibility of using an external standard analytical curve, which presented adequate linearity, with low values of LOD and LOQ (0.084 mg L-1 and 0.255 mg L-1, respectively). In addition, the developed method showed adequate precision (RSD <20%) and accuracy (recovery rates of 80-110%). Then, the composition of twenty samples of cane syrups was evaluated in terms of pH, acidity, reducing sugars, total sugars, soluble solids, conductivity ash, ICUMSA color and reducing capacity. Great variation between samples was observed regarding these parameters. However, most of the samples presented values within the limits established by the Brazilian legislation for these parameters. Regarding the elemental composition, cane syrup samples showed variable concentrations of Na, K, P, Ca, Mg, Fe, Mn, Zn, Cu and Cr. Considering the recommended daily intake of minerals, most of the evaluated samples proved to be a good source of Mg, Fe, Mn and Cr. In addition, the bioaccessibilities of Mg, Fe, Mn, Zn and Cu were evaluated by means of in vitro digestion assays and most of the samples showed high bioaccessibility of these elements (on average 79.8; 75.9; 76.3; 98.0 and 79.6%, respectively). These results encourage the valorization of cane syrups as sources of minerals and its use as an ingredient in the foods and beverages industries. Regarding fruit flours samples, high variability was observed concerning the content of dietary fibers (7.5 to 69.7 g 100 g-1), carbohydrates (4.1 to 74.9 g 100 g-1), proteins (2.9 to 12.9 g 100 g-1), ash (1.0 to 7.0 g 100 g-1), lipids (1.0 to 8.1 g 100 g-1) and total phenolic contents (2.9 to 41.0 mg GAE g-1), besides the energetic contribution (339 to 420 kcal 100 g-1). Fruit flours also showed high variability in mineral contents and most of the analyzed flours provide an adequate contribution to the daily mineral requirements (especially Mg, Fe, Mn and Cu) with a daily intake of 30 g. On the other hand, low bioaccessible fractions were obtained for Ca (18.0%) and Fe (28.9%), while Mg was the most bioaccessible mineral (81.5%), followed by Zn (67.8%), Cu (66.4%) and Mn (55.5%). Significant correlations were observed between the minerals bioaccessibility and dietary fiber, ash, lipids and total phenolic contents. However, fruit flours prove to be important sources of Mn and Cu, besides the contribution to daily fiber intake and high contents of phenolic compounds.